2013
DOI: 10.1016/j.juro.2013.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Increased mRNA Expression of Genes Involved in Pronociceptive Inflammatory Reactions in Bladder Tissue of Interstitial Cystitis

Abstract: This study showed increased expression of the genes involved in pronociceptive inflammatory reactions in interstitial cystitis, including TRPV1, 2 and 4, ASIC1, NGF and CXCL9, and to our knowledge TRPM2 for the first time. The different expression patterns suggest distinct pathophysiologies for classic and nonclassic interstitial cystitis. The genes and their products are potential candidates for use as biomarkers or novel therapy targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 27 publications
3
81
0
1
Order By: Relevance
“…It is possible (although not very likely) that patients participating in the interstitial cystitis trials had reduced RTX sensitivity due to an overproduction of TRPV1b. Finally, it is worth mentioning here that in bladder biopsies taken from patients with interstitial cystitis only TRPM2 and TRPV2 correlated with disease severity (Homma et al, 2013). Thus, it is entirely possible that (unlike in experimental animals) TRPV1 does not play any major role in the pathogenesis of interstitial cystitis.…”
Section: Transient Receptor Potential Channels As Therapeutic Targmentioning
confidence: 80%
See 1 more Smart Citation
“…It is possible (although not very likely) that patients participating in the interstitial cystitis trials had reduced RTX sensitivity due to an overproduction of TRPV1b. Finally, it is worth mentioning here that in bladder biopsies taken from patients with interstitial cystitis only TRPM2 and TRPV2 correlated with disease severity (Homma et al, 2013). Thus, it is entirely possible that (unlike in experimental animals) TRPV1 does not play any major role in the pathogenesis of interstitial cystitis.…”
Section: Transient Receptor Potential Channels As Therapeutic Targmentioning
confidence: 80%
“…A complex change in mRNA levels encoding TRP channels was recently reported in bladder biopsies taken from 22 patients with classic interstitial cystitis and 17 patients with nonclassic interstitial cystitis (Homma et al, 2013). In patients with nonclassic (i.e., nonulcerated) interstitial cystitis, TRPV2 was the only TRP channel to show increased expression.…”
Section: Transient Receptor Potential Channels: Acquired Diseasesmentioning
confidence: 84%
“…These reports have been followed by many others that showed significantly abnormal expression of additional urothelial proteins and proteoglycans in bladder biopsies from BPS/IC patients as compared to controls, including decreases in chondroitin sulfate proteoglycans (both groups hydrodistended prior to biopsy) [9, 30]; uroplakin (both groups hydrodistended prior to biopsy) [9]; neurokinin receptor 1 (only BPS/IC patients underwent uroflowmetry, postvoid residual and urodynamic investigations) [10]; and the urothelial tight junction proteins zonula occludens 1 [9, 10], junctional adhesion molecule 1, occludin, and claudin 1 [10]. BPS/IC bladder biopsies have also been shown to have increased expression of many other bladder urothelial cell genes including nerve growth factor (all control groups also hydrodistended prior to biopsy in [31]; only BPS/IC group hydrodistended prior to biopsy in [32]), E-cadherin (both BPS/IC and control specimens obtained after hydrodistention) [9], inducible nitric oxide synthase (unclear whether some BPS/IC patients and controls did not undergo hydrodistention prior to biopsy) [33, 34], caveolin 1 (no mention of hydrodistention for BPS/IC patients or controls) [35], vascular endothelial growth factor (only BPS/IC patients hydrodistended prior to biopsy) [36], human chorionic gonadotropin beta (no mention of hydrodistention for BPS/IC patients or controls) [37], claudin 2, and a variety of cell signaling receptors including bradykinin B(1) receptor, cannabinoid receptor CB1, muscarinic receptors M3–M5 [10], and transient receptor potential vanilloid 2 (TRPV2) [32]. Increased activated (nuclear) NF κ B was also evident in BPS/IC bladder urothelial cells [38].…”
Section: Bladder Urothelial Cell Gene Expression and Function In Bmentioning
confidence: 99%
“…60 Nickel et al 65 also proposed that a phenotype-directed therapeutic approach can significantly improve the treatment outcome. Homma and colleagues 66 showed that there are different gene expression patterns for classic and nonclassic IC. Tripp and coworkers 67 developed a system to classify IC/BPS into several pain-location phenotypes, and suggested that the system can enable patients to receive better treatment as it can provide improved pain management.…”
Section: Reclassification Of Ic/bpsmentioning
confidence: 99%